Addition of the leaf fiber of pineapple (Ananas comosus (L) Merr) to the impact strength test of heat cured acrylic resin: Penambahan serat daun nanas (Ananas comosus (L) Merr) pada uji kekuatan impak basis resin akrilik polimerisasi panas - Ni Kadek Sugianitri; Suhendra (Makassar Dental Journal, 2021)
Heat cured acrylic resin is a dental material that widely used as removable denture base due to its biocompatible, easy to obtain, inexpensive and ease of processing but has a disadvantage of being fracture. The purpose of this study was to determine the diffe-ference in the impact strength test of the HCAR after adding pineapple leaf fibre. Post-test only control groups design was used as laboratory experimental. This research divided into 4 groups, those are without addition pineapple leaf fibres, addition of 5%, 10%, 15% pineapple leaf fibres. Impact strength was performed by charphy impact test. After getting the mean results of the im-pact test, the Kruskal Wallis test was then performed that showed that there is a significant difference between the group without addition pineapple leaf fibre and the group with the addition of pineapple leaf fibre a significance of p-value 0.001 (p<0.05). The plate without addition of pineapple leaf fibre, has a higher impact strength than the concentration of 5%, 10% and 15%. So it can be concluded that the addition of too high concentration pineapple leaf fibre causes the impact strength of the acrylic resin decreased.